2014
DOI: 10.1523/jneurosci.2039-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Alpha- and Beta-Band Oscillations during Mental Simulation of Goal-Directed Actions

Abstract: Rhythmic neural activity within the alpha (8 -12 Hz) and beta (15-25 Hz) frequency bands is modulated during actual and imagined movements. Changes in these rhythms provide a mechanism to select relevant neuronal populations, although the relative contributions of these rhythms remain unclear. Here we use MEG to investigate changes in oscillatory power while healthy human participants imagined grasping a cylinder oriented at different angles. This paradigm allowed us to study the neural signals involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
140
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 67 publications
23
140
2
4
Order By: Relevance
“…This rotation would arguably require a greater level of processing, and may explain Frenkel-Toledo and colleagues ' (2013) finding that an allocentric perspective of a movement induced greater -suppression compared to an egocentric perspective, as it is known that sensorimotor suppression is enhanced by task demands and cognitive load (Klimesch, Schimke, & Pfurtscheller, 1993;Klimesch et al, 1998;Brinkman et al, 2014). However, we did not observe a significant effect for the factor perspective, suggesting that this possibility is unlikely.…”
Section: Involvement Of  In Processing Of Allocentric Hands Movementmentioning
confidence: 48%
“…This rotation would arguably require a greater level of processing, and may explain Frenkel-Toledo and colleagues ' (2013) finding that an allocentric perspective of a movement induced greater -suppression compared to an egocentric perspective, as it is known that sensorimotor suppression is enhanced by task demands and cognitive load (Klimesch, Schimke, & Pfurtscheller, 1993;Klimesch et al, 1998;Brinkman et al, 2014). However, we did not observe a significant effect for the factor perspective, suggesting that this possibility is unlikely.…”
Section: Involvement Of  In Processing Of Allocentric Hands Movementmentioning
confidence: 48%
“…Within cortex, the sensorimotor ␤-rhythm is classically thought to arise from motor, rather than somatosensory, regions (Brovelli et al 2002;Pfurtscheller et al 1997) and, therefore, has been mainly considered as a motor rhythm. In line with this, there is extensive evidence for a modulation of this rhythm by most aspects of movement: from movement execution (Jasper and Penfield 1949;Rougeul et al 1979), offset (Pfurtscheller et al 1997(Pfurtscheller et al , 1998, planning (Leocani et al 1997), preparation (Pfurtscheller et al 1998;Zhang et al 2008), inhibition (Pogosyan et al 2009;Swann et al 2009), and switching (Cheyne et al 2012;Gilbertson et al 2005;Stoffers et al 2001), to movement imagery (Brinkman et al 2014;Schnitzler et al 1997) and observation (Babiloni et al 2002;Koelewijn et al 2008;Orgs et al 2008, Pavlidou et al 2014. Furthermore, strong evidence for the motor function of the sensorimotor ␤-rhythm comes from the clear ␤-peak in the corticomuscular coherence: the coherence between the extracranial activity over the sensorimotor cortex and the EMG (Baker et al 1997;Salenius et al 1997).…”
Section: The Sensorimotor ␤-Rhythmmentioning
confidence: 69%
“…According to this popular theory, the BG 12 circuit is able to process those requests and finally select the most salient (or urgent) 13 potential action, via the direct BG pathway, while providing inhibition to the rest 14 competing channels via the indirect pathway [6,7]. 15 An increasing amount of neurophysiological evidence implicates the BG to selection 16 of voluntary motor actions and provides indirect verification of this hypothesis [8]. [9] 17 showed that the excess activation of the direct BG pathway in freely behaving mice, via 18 stimulation of MSN D1 neurons in the striatum, increases movement, while the 19 stimulation of the indirect pathway made the same animals to freeze.…”
mentioning
confidence: 99%
“…In addition, 20 although both pathways are required for healthy action selection and were found to 21 contribute equally to the initiation of actions in [10], the indirect pathway is suppressed 22 during the execution of actions or action sequences [11], presumably because any 23 behavioural conflicts have already been resolved during movement [8]. 24 From another standpoint, low-frequency brain oscillations have been widely 25 implicated in both the function of the BG [12] and the process of decision 26 making [13][14][15][16][17]. Oscillations in the cortex mediate the processing of new 27 information [18], the dynamic formation of neural ensembles representing different 28 actions and the suppression of other task-irrelevant regions [19,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation